Peningkatan Kinerja Guru melalui Supervisi Edukatif Kolaboratif secara Periodik - Noor, Muhammad (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this study was to describe the steps of collaborative educative supervision periodically in preparing learning plans, implementing learning, assessing learning achievement, carrying out follow-up on student achievement learning. This research was carried out at MI Missbahussalam Sungai Punggu Lama Subdistrict Anjir Muara there was the 2017/2018 school year. This research is an action research and carried out two cycles with the stages of action preparation, action implementation, monitoring and evaluation, and reflection. Data collection techniques in this study consisted of four main activities, namely the initial data collection, data analysis results at the end of each cycle, and other responses from the teacher on the implementation of collaborative supervision of educational models. The data has been collected and then analyzed by using qualitative and quantitative analysis. Qualitative analysis is used to explain changes in teacher behavior in learning and supervisor behavior in implementing teacher supervision. The results showed that with peer supervision and collaborative educative can improve teacher performance in preparing learning plans, implementing learning, assessing learning achievement and follow-up on the results of assessment of student learning achievement.